2022
DOI: 10.1007/s10164-022-00749-y
|View full text |Cite
|
Sign up to set email alerts
|

Locomotion and flow speed preferences in natural habitats by large water striders, Ptilomera tigrina, with micro-morphological adaptations for rowing

Abstract: Water strider (Gerridae) morphology and behavior have become the focus of interdisciplinary research in biological diversification and bio-inspired technology. However, the diversity of behaviors and morphology of the large-sized Gerridae have not been intensely studied. Here, we provide locomotory behaviors and legs’ micro-morphology of the large South-East Asian water strider, Ptilomera tigrina. Using high-speed videography and experiments in natural habitats, as well as scanning electron microscopy of midle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 52 publications
4
11
0
Order By: Relevance
“…The difference between G. gigas, who lives in slower flowing waters, and P. tigrina, who lives in faster moving water, is consistent with the idea that even though the asymmetric sliding always creates less resistance than the symmetric sliding and does not cause sinking regardless of body mass and leg geometry, P. tigrina does not use the asymmetric sliding (exception shown in Supplementary Movie 4; description of movie in SM7) because of the importance of strong thrust in the very frequent short strides against the fast flowing water in their habitat 47 (see also Supplementary Movie 3 described in SM7). Hence, we propose that the habitat type may affect the evolutionary trajectories shaping the wetted leg geometry in large water striders leading to the asymmetrical locomotion in slow-flowing waters and to the long-foreleg/symmetrical locomotion combination in species from fast currents, where the requirements for frequent and strong thrust may additionally trigger evolution of special micro-structures for rowing 41,47,51 and the associated loss of the midlegs' function of supporting the water strider on water surface 33,47 . If this is correct, then Gerridae illustrate how the physical environment channels the morphological and behavioral evolution 52,53 towards either of the two physically feasible adaptive solutions for locomotion by large-sized water striders.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…The difference between G. gigas, who lives in slower flowing waters, and P. tigrina, who lives in faster moving water, is consistent with the idea that even though the asymmetric sliding always creates less resistance than the symmetric sliding and does not cause sinking regardless of body mass and leg geometry, P. tigrina does not use the asymmetric sliding (exception shown in Supplementary Movie 4; description of movie in SM7) because of the importance of strong thrust in the very frequent short strides against the fast flowing water in their habitat 47 (see also Supplementary Movie 3 described in SM7). Hence, we propose that the habitat type may affect the evolutionary trajectories shaping the wetted leg geometry in large water striders leading to the asymmetrical locomotion in slow-flowing waters and to the long-foreleg/symmetrical locomotion combination in species from fast currents, where the requirements for frequent and strong thrust may additionally trigger evolution of special micro-structures for rowing 41,47,51 and the associated loss of the midlegs' function of supporting the water strider on water surface 33,47 . If this is correct, then Gerridae illustrate how the physical environment channels the morphological and behavioral evolution 52,53 towards either of the two physically feasible adaptive solutions for locomotion by large-sized water striders.…”
Section: Discussionsupporting
confidence: 77%
“…S13), that there are two solutions: either a shift to "long-foreleg geometry" by elongation of forelegs (recent studies in the genetics of morphology in Gerridae identified some genes that may be involved in the leg elongation 49,50 while maintaining the standard symmetric locomotion mode like in Ptilomerinae, or a use of asymmetric locomotion mode, like in G. gigas. The difference between G. gigas, who lives in slower flowing waters, and P. tigrina, who lives in faster moving water, is consistent with the idea that even though the asymmetric sliding always creates less resistance than the symmetric sliding and does not cause sinking regardless of body mass and leg geometry, P. tigrina does not use the asymmetric sliding (exception shown in Supplementary Movie 4; description of movie in SM7) because of the importance of strong thrust in the very frequent short strides against the fast flowing water in their habitat 47 (see also Supplementary Movie 3 described in SM7). Hence, we propose that the habitat type may affect the evolutionary trajectories shaping the wetted leg geometry in large water striders leading to the asymmetrical locomotion in slow-flowing waters and to the long-foreleg/symmetrical locomotion combination in species from fast currents, where the requirements for frequent and strong thrust may additionally trigger evolution of special micro-structures for rowing 41,47,51 and the associated loss of the midlegs' function of supporting the water strider on water surface 33,47 .…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…The copyright holder for this this version posted October 31, 2022. ; https://doi.org/10.1101/2022.10.28.514156 doi: bioRxiv preprint and strong thrust may additionally trigger evolution of special micro-structures for rowing (Mahadik et al, 2020;Kim et al, 2022;Polhemus and Zettel, 1997) and the associated loss of the midlegs' function of supporting the water strider on water surface (Andersen, 1976;Kim et al, 2022). If this is correct, then Gerridae illustrate how the physical environment channels the morphological and behavioral evolution (Dobzhansky, 1974;Martínez and Moya, 2011) towards either of the two physically feasible adaptive solutions for locomotion by large-sized water striders.…”
Section: Discussionmentioning
confidence: 99%